Different solutions to similar problems: parents' reasons for choosing to homeschool and social criticism of the education system. Issue 1 (2nd January 2021) - Neuman, Ari; Oz, Guterman
Abstract: The article addresses the way in which characteristics of the education crisis in the postmodern era are manifested in parental deliberations when choosing to homeschool their children in Israel. Based on a review of the characteristics of the education crisis and examination of possible solutions, homeschooling is presented as an optional solution to this crisis. The article is based on a qualitative study that examined the reasons of Israeli parents for selecting homeschooling, which demonstrates the link between the deliberation process of those choosing homeschooling and the characteristics of the education crisis. The article ends with an explanation about why it is important to regard homeschooling as a unique solution. Highlights: Education crisis characteristics. Possible solutions for the education crisis. Home education as one of the possible solutions for the education crisis. Link between the deliberation process of those choosing home education and the education crisis. The importance of regarding home education as one of the solutions to the crisis in education.